2012
DOI: 10.1063/1.3671959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dust charging and trapped electrons on nonlinear solitary structures in an inhomogeneous magnetized plasma

Abstract: Main concerns of the present article are to investigate the effects of dust charging and trapped electrons on the solitary structures evolved in an inhomogeneous magnetized plasma. Such a plasma is found to support two types of waves, namely, fast wave and slow wave. Slow wave propagates in the plasma only when the wave propagation angle θ satisfies the condition θ≥tan-1{(1+2σ)-[(ndlh(γ1-1))/(1+ndlhγ1)]-v0u0}, where v0(u0) is the z- (x-) component of ion drift velocity, σ = Ti/Teff, ndlh = nd0/(nel0 + neh0), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…On the other hand, since the width of shock structures is directly proportional to the dispersion coefficient, the increase in strength of magnetic field tends to decrease the width of shocks structures and makes them narrower. Similar kind of behavior was observed by Kumar et al [44]. Figure 8 illustrates the variation of shock structures with magnetic field in 3D.…”
Section: Parametric Analysis Of Dust Acoustic Shock Structuressupporting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, since the width of shock structures is directly proportional to the dispersion coefficient, the increase in strength of magnetic field tends to decrease the width of shocks structures and makes them narrower. Similar kind of behavior was observed by Kumar et al [44]. Figure 8 illustrates the variation of shock structures with magnetic field in 3D.…”
Section: Parametric Analysis Of Dust Acoustic Shock Structuressupporting
confidence: 67%
“…The obliquely propagating ion-acoustic (IA) solitons in a magnetized and weakly relativistic warm plasma have been investigated by deriving KdV equation and it was inferred that the soliton energy is lowered by stronger magnetic field and the solitons become narrower [41]. Furthermore, the effect of ion temperature and dust charging on characteristics of ion-acoustic (IA) solitons in a magnetized inhomogenous plasma has been reported by Malik [43] and Kumar et al [44] respectively. The propagation properties of compressive solitons were analyzed by Malik and Malik [47] in a dusty plasma comprising of electrons, positrons and dust grains of either positive or negative charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that in the previous studies, dust particles have been neglected by the researchers, which become important plasma species in the Hall thrusters due to the erosion of the wall of the chamber and sputtering [22,23]. In general, it is found that current carried by the highly mobile electrons plays the important role in dust charging, and as a result, the dust particles are negatively charged in the plasma [24][25][26][27][28][29]. The & Hitendra K. Malik hkmalik@hotmail.com negatively charged dust particles will hinder the movement of ions and, hence, alter the thrust and efficiency of the thruster.…”
Section: Introductionmentioning
confidence: 99%
“…Such a difference causes different dynamics for these two type of plasmas, including shocks and solitary waves. For example, the formation and excitation of nonlinear solitary waves in inhomogeneous magnetized plasmas having negative ions have been studied in Malik & Kawata (2007), Malik & Stroth (2008), Singh & Malik (2008) and the nonlinear solitary waves in plasmas including (impurity) dust particles in (Kumar & Malik 2011; Kumar, Malik & Singh 2012; Malik & Malik 2014). Also, the difference is important from another aspect, that is, dust particles differ from negative ions in that their charge is not a fixed quantity and therefore, this can also cause different dynamics.…”
Section: Introductionmentioning
confidence: 99%